Precision Medicine: Global landscape and its Strategic Imperative for Bangladesh (Journal of Rangpur Medical College, 2025)
Precision medicine (PM) is a fundamental transformation in healthcare, moving from a reactive, "one-size-fits-all" model to a proactive approach based on individual variability in genes, environment, and lifestyle. This review summarizes the global landscape of PM on its technological drivers, clinical applications, and associated ethical challenges. It then critically analyzes the nascent state of PM in Bangladesh on the existing infrastructure, formidable barriers, and potential opportunities. The article concludes with a strategic roadmap, emphasizing that for Bangladesh to employ PM's potential for its dual disease burden, a coordinated national strategy focusing on infrastructure, workforce development, and ethical governance is not just beneficial but essential.J Rang Med Col. 2025 Sep;10(2): 163-165